HUBUNGAN MEKANIKA TUBUH PERAWAT DENGAN RESIKO TERJADINYA LOW BACK PAIN (LBP) PADA PERAWAT PELAKSANA DI RUMAH SAKIT UMUM DR PIRNGADI MEDAN - Purba, Bunga Theresia; Sipayung, Normi; Syapitri, Henny (JURNAL HEALTH REPRODUCTIVE, 2019)
Perform ungood of body mechanics is one of the causes of the risk of Low Back Pain (LBP). Which if left untreated can seriously lifelong paralysis. This study aims to look the relationship between body mechanics of nurse with the risk of Low Back Pain (LBP) at the Dr.Pringadi General Hospital, wits 41 nurses. Results of this study showed the body mechanics of nurse are good (25 people or 62,5% ) and the risk for Low Back Pain (LBP) are 33 people (82,5%). Resuts of this study wits fisher’s exact test p=0,007 (P < 0,05) means that there were hare relationship between the nurse’s body mechanics with occurrence risk Low Back Pain (LBP) of the nurses in the Dr. Pirngadi General Hospital. From these results, it is expected to increase the knowledge of nurses and to inform the nurses and to inform the nurse so much more attention to body mechanics when performing each action the patient to improve the quality of hospital care through a batter nurse.